2016
DOI: 10.1080/02688697.2016.1253827
|View full text |Cite
|
Sign up to set email alerts
|

Post-craniotomy intracranial infection in patients with brain tumors: a retrospective analysis of 5723 consecutive patients

Abstract: Risk factors for PCII can be identified early in the perioperative period. These findings raise the possibility of improving the clinical outcomes of patients with brain tumors who undergo craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 25 publications
7
52
7
1
Order By: Relevance
“…The mortality rate of PCNSIs dropped drastically in past years, from 34% in 2005 [36] to 19% in 2011 [37], and a recent study reported that the mortality was 3.6% [16]. The mortality of present study was relatively higher than those reported, which was 21.7%.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The mortality rate of PCNSIs dropped drastically in past years, from 34% in 2005 [36] to 19% in 2011 [37], and a recent study reported that the mortality was 3.6% [16]. The mortality of present study was relatively higher than those reported, which was 21.7%.…”
Section: Discussioncontrasting
confidence: 56%
“…Microbial culture and identification remain the gold standard for diagnosing bacterial meningitis [13,14]. However, with the widespread applications of prophylactic antibiotics, the culture-positive rate of infection was relatively low, reporting from 7.5% to 50% [15][16][17]. In our study, all patients received 1.0 g cephalosporin as prophylactic therapy, which might lead to the relative lower CSF culture positive rate (29.1%).…”
Section: Discussionmentioning
confidence: 72%
“…Postoperative central nervous system infections (PCNSIs) are an uncommon but serious complication in neurosurgery, with an infection rate ranging from 4.5% to 7.4% (1,2). Due to the advent of the sterile field and prudent antibiotic use during the perioperative period, the overall mortality rate of PCNSIs has dropped drastically in the past several years, from 34% in 2005(3) to 1.8% in a recent study; however, this mortality rate is still 3.78 times that of non-PCNSI patients (2). Although most PCNSIs are caused by gram-positive bacteria, there has been a trend toward gram-negative organisms in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a certain percent of CCM patients having postoperative infection-related complications. These complications, including pneumonia and intracranial infection, are among the most serious and life-threatening complications after CCM surgery and are associated with poor short-and long-term outcomes 6,7 . For CCM patient with infection-related postoperative complications, a prolonged clinical course is needed.…”
mentioning
confidence: 99%